Eye Biometry Shift after Scleral Buckling Procedure - A. N. Kulikov; E. V. Danilenko; A. R. Kuznetsov (Oftalʹmologiâ, 2022)
Background. There are a great number publications presenting results of various types of optical and ultrasound biometry before and after scleral buckling (SB).Patients and methods. Biometry was performed for 22 eyes of 22 patients before and after surgical treatment of rhegmatogenous retinal detachment. We used 4 types of optical (IOLMaster 500, IOLMaster 700, Lenstar LS 900 and REVO SOCT Copernicus) and 2 types of ultrasound biometry (A- and B-scan).Results. According to the all biometry data, there was an increase in the axial lens (AL) (the maximum value of eye elongation according to IOLMaster 500 data was 0.84 ± 0.69 mm, p = 0.000), swallowing of the anterior chamber depth (ACD) in regard to IOLMaster 700 (0,48 ± 0,32 mm, p = 0.000) and lens thickness (LT) augmentation (according to A-scan data the largest thickening was 0.17 ± 0.59 mm, p = 0.064).Conclusions. The anatomy of the eye reliably changes after SB implantation due to increase in the AL, ACD swallowing and an LT augmentation, that makes changes in IOL power calculation with modern formulas during combined surgery. Lenstar LS 900 is the preferred method of biometry when planning simultaneously lens exchange with SB procedure.